Analisis Efektivitas dan Keandalan Mesin Single Screw Extruder Guna Penyusunan Penjadwalan Preventive Maintenance (Studi Kasus : PT. Tjakrindo Mas Gresik) - Ragata Penta Fauzany; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research was conducted on a Single Screw Extruder machine in the Water Treatment Plant Division of PT. Tjakrindo Mas Gresik, which is used to produce 1-inch Excellon PTH 4 PVC pipes. The study aims to analyze machine effectiveness, identify the causes of low performance, calculate component reliability, and formulate recommendations for Preventive Maintenance schedules along with maintenance cost estimations. The issues identified include downtime, defective products, high setup times, and damage to the machine's main components. The object of this research covers six main components: the Motor and Gearbox, Thrust Bearing, Hopper and Feed Throat, Barrel, Screw, and Die. The methods applied include Overall Equipment Effectiveness (OEE), Root Cause Analysis (RCA), Fishbone Diagram, 5 Whys, and reliability analysis through the calculation of TTF, TTR, TBF, MTTF, MTTR, MTBF, Failure Rate, Repair Rate, Availability, and Reliability. The results of the study are expected to determine critical components, optimal maintenance intervals, and improve machine reliability, product quality, and maintenance cost efficiency.